Constructing a Marketing Communication Plan for a Start-up Cloud-Based Manufacturing (CBM) Firm: The Case Study of Co-Fabrico - Kasidi, Irfan Handaru (2017)
This report is made to develop a marketing communication plan for a start-up Cloud-based Manufacturing (CBM) firm, Co-Fabrico. The company is based in Nottingham, United Kingdom and has been in the business for two years. Co- fabrico is currently in a crucial period where it is eager to get more members to establish online trading to keep the business running. This report is expected to provide some insight and recommendation based on communication theory. As the result of this marketing communication plan, Co-Fabrico would be able to improve its presence within the industry to gain more members.